PEMBEBASAN NARAPIDANA DALAM BENTUK PENANGANAN COVID-19 - Devita Marentina Putri Larasati (Muhammadiyah Law Review Journal, 2022)
The government policy to free the convict in the middle of pandemic covid-19 have reaped controversy in the community. some have raised objections with concerns about increased crime and impact policy from freedom of the convict is temporary solution. The step is assessed for stop spread and transmission covid-19 at jail facilities because the main factor spread pain at the jail is government policy which still prioritizes imprisonment in law enforcement. This legal research uses empirical juridical research which uses statutpry approach with qualitayive kualiti for search, prosses, and analyze result of the research with descriptive. Policy the freedom convict in an effort to suppres the transmission of covid-19 based on concern government with transmission on the jail. However, released prisoners do not automatically guarantee that they are protected from the virus. Another problem is the difficulty in fulfilling their daily needs, namely due to the difficulty of finding work so that there is great potential for former inmates to commit criminal acts again. Apart from fulfilling the necessities of life, another factor that encourages recidivists is the ineffectiveness of the supervisory function by the Correctional Center (Bapas). this is due to the limited human resources in Bapas itself and it is also known that Bapas does not conduct guidance in the usual way, currently only relies on existing technology, so it cannot provide optimal services.